2014
DOI: 10.1007/s00401-014-1319-6
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological spectrum of paediatric diffuse intrinsic pontine glioma: diagnostic and therapeutic implications

Abstract: Diffuse intrinsic pontine glioma (DIPG) is the main cause of brain tumour-related death in children. In the majority of cases diagnosis is based on clinical and MRI findings, resulting in the scarcity of pre-treatment specimens available to study. Our group has developed an autopsy-based protocol to investigate the histologic and biologic spectrum of DIPG. This has also allowed us to investigate the terminal pattern of disease and gain a better understanding of what challenges we are facing in treating DIPG. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
269
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(296 citation statements)
references
References 26 publications
(37 reference statements)
23
269
2
2
Order By: Relevance
“…However, it should be noted that there were only 2 patients with a mixed neuronal/glial tumor and thus a larger population size is needed to accurately assess the survival rates of these types of neoplasms. These results are consistent with other studies that have patients with these diffuse intrinsic brainstem gliomas experiencing poor prognosis and survival outcomes of < 10% at 2 years in some cases [29]. Pilocytic astrocytomas tend to have much better outcomes with lower recurrence rates and a less aggressive invasion of the surrounding parenchyma [15].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, it should be noted that there were only 2 patients with a mixed neuronal/glial tumor and thus a larger population size is needed to accurately assess the survival rates of these types of neoplasms. These results are consistent with other studies that have patients with these diffuse intrinsic brainstem gliomas experiencing poor prognosis and survival outcomes of < 10% at 2 years in some cases [29]. Pilocytic astrocytomas tend to have much better outcomes with lower recurrence rates and a less aggressive invasion of the surrounding parenchyma [15].…”
Section: Discussionsupporting
confidence: 82%
“…Neoplastic location and histological grade were not associated with any significant influence on overall survival in their cohort. Other studies have also shown dismal survival outcomes even with radiotherapy and surgery in cohorts expressing the H3 K27M mutations compared to wild-type tumors [26-29]. With treatment options for this type of histologically unique neoplasm lacking, more needs to be done to better understand their pathology and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies with more patients may provide additional insight and be helpful to assess the relative difference between baseline and follow-up 18 F-FDG PET histogram metrics in the evaluation of children with DIPG. With genomic analyses of DIPG from biopsies improving knowledge of associated mutations (such as K27M-H3.1 mutations) (36)(37)(38), ADC (39) and PET histogram analyses may be incorporated into future prospective DIPG treatment protocols.…”
Section: Discussionmentioning
confidence: 99%
“…These clinically aggressive tumors are appropriately designated WHO grade IV regardless of traditional diffuse glioma histological grading criteria [2,13] . The major predictor of overall survival for patients with pontine gliomas is the histone mutation status [13] .…”
Section: Prognosis and Treatmentmentioning
confidence: 99%
“…These clinically aggressive tumors are appropriately designated WHO grade IV regardless of traditional diffuse glioma histological grading criteria [2,13] . The major predictor of overall survival for patients with pontine gliomas is the histone mutation status [13] . Children with pontine gliomas harboring the K27M-H3.3 mutation have an average overall survival of less than 1 year [8,13,14] , and fewer than 10% of patients survive to 2 years [2] .…”
Section: Prognosis and Treatmentmentioning
confidence: 99%